(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
ZBB is an effective tool to maneuver organizations of better allocation of their financial and non-financial resources. In application, this method puts a requirement for each organization to re-evaluate annually its activities from the zero ground. It necessitate for an effective budget procedure is increasingly apparent in business enterprises, so as to face the appareling operating costs and declining growth rates. In this present era of hectic competition, inflation technological advancement of world wide, lofty costs of production and distribution & depleting resources, no organization can be able to survive and flourish unless it adopts an effective approach to budgeting system. ZBB is a significant technique in which unneeded expenditures are eradicate from the proposed budget. This paper, elaborate the concept, definitions, budgeting process, decision units, decision packages, benefits and lacunas of ZBB. ZBB presents an opportunity for organizations to cut costs and improve quantitative and qualitative aspects of operations.Despite increasing popularity and interest, comprehensive ZBB cycles are not a cost-effective option for most organi¬zations in either the public or private sectors. However, ZBB components and theory may be useful in specific sectors under specific circumstances. Although the economic envi¬ronment has driven renewed interest in ZBB, more practical and less costly budgeting alternatives are available that can meet organizational needs.